Second generation migrants and school. From educational needs to social inclusion - Tiziana Chiappelli (University of Bologna, 2021)
This article analyzes the testimonies of new generations of immigrant origin on inclusive education, gathered through three methods of research and intervention: the first is linked to the Region of Tuscany and CNR - ITTIG's #IOPARTECIPO project, funded by AMIF; the second involves interviews and focus groups conducted for research by the Italian Authority for Children and Adolescents, titled, L'inclusione e la partecipazione delle nuove generazioni di origine immigrata. Focus sulla condizione femminile, while the third one, Apriti Sesamo, funded by FAMI, is still ongoing. These projects, developed from June to 2018, witnessed the participation of over 100 second-generation children. Though not a statistically significant sample, a qualitative analysis of the interviews and discussion groups has proved itself extremely significant, offering ample points of reflection and opportunities for in-depth analysis. This article will investigate the issues raised by the children in regard to their educational paths and relationships with peers, the latter identified as instrumental to their education and an essential indicator for assessing real social integration.